Salt industry by-products on lettuce growth and yield in hydroponic culture (Asian-Australasian Journal of Food Safety and Security, 2025)
Lettuce (Lactuca sativa L.) is a nutrient-rich leafy vegetable commonly raw consumed and grown in soilless systems that often rely on expensive chemical fertilizers. Exploring sustainable nutrient alternatives like salt industry by-products (SIB) can reduce input costs and environmental impact. This study aimed to evaluate the effect of SIB as a partial nutrient source on lettuce growth, yield, and nutritional quality in a soilless culture system. The experiment was conducted at the Central Laboratory of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh from September 2014 to March 2015. The base nutrient solution contained NO₃-N (17.05 meqL⁻¹), P (7.86 meqL⁻¹), K (8.94 meqL⁻¹), Ca (9.95 meqL⁻¹), Mg (6.0 meqL⁻¹), S (6.0 meqL⁻¹), and micronutrients Fe (3 ppm), B (0.5 ppm) , Zn (0.1 ppm) , Cu (0.03 ppm), Mo (0.025 ppm), and Mn (1 ppm). Treatments included 0 (control), 0.5 and 0.75 mlL⁻¹ SIB. The control produced the highest plant height, leaf number, breadth, length, and fresh weight, while 0.75 mlL⁻¹ SIB-treated plants exhibited the lowest growth but the highest ascorbic acid (157.61 mg/100 g) and beta-carotene (3.21 mg/100 g) contents. The 0.5 mL L⁻¹ SIB treatment resulted in moderate yield with balanced nutritional quality, indicating comparable leaf area, relative growth rate, and net assimilation rate to the control. It can therefore be concluded that 0.5 mL L⁻¹ SIB may serve as a sustainable nutrient supplement in hydroponic lettuce production. This finding emphasizes the potential of utilizing salt industry by-products as an eco-friendly and cost-effective nutrient source in soilless cultivation systems.Asian Australas. J. Food Saf. Secur. 2025, 9(2), 67-76